Perspectivas hermenêuticas de Isaías 45,1-7: Uma análise do título messiânico atribuído a Ciro. - Silva, Roberto de Jesus (2013)
The book of the prophet Dêutero-Isaiah approaches that Javé comes to console its people exiled in Babylonia. Foreign king Cyrus, in the text of Is 45,1-7 is intitled of Messiahs de Javé. Therefore, this research has as objective to reflect on the messianic heading attribution to king Cyrus, in the context of the Babylonian exile. For this, I analyze some contributions of diverse authors and authors of the Biblical area, exploring the diversity of analyses on this subject. It has many interpretations on the meaning of the messianic heading attributed to the king Cyrus, between them, it has who defines Cyrus as the Messiahs de Javé, that is, Cyrus as liberating of the exiled ones and not as the substitute of the messianic hope in a Messiahs proceeding from the house of David. In this work, I still argue has messianic hope, manifest in the exilic period and after-exilic, detaching the faith that the messianic communities exerted in these periods. At last, I analyze the messianic of the neo-testamentary communities after-macabaicas and in the attempt discovering if Cyrus was one messianic figure, in these periods.